Control Environment of Linear Induction Drive Dynamics Models - Rinkevičienė, R.; Lisauskas, S. (Elektronika ir elektrotechnika, 2007)
Developed dynamic models of linear induction drives allow examining various dynamic characteristics of linear induction drives according to results of simulation. Nevertheless, changes in motor windings connection way or motor parameters require recalculating and renewing set up of model parameters. The integrated control environmental of model is discussed. Developed software allows controlling model and investigating non-symmetrical modes of single phase breaking and breaking by direct current, compare obtained characteristics and examine influence of motor parameters on that. Active program window is presented, where the motor parameters, winding connection way, operation mode and desired simulation results can be set up. Algorithm of simulation program and algorithm for processing of simulation results are presented. Breaking time dependence on the resistance of the secondary element has minimum value. Presented dependence of breaking time against resistance of the secondary element and the breaking voltage allows choosing these parameters for obtaining of desirable braking time. Ill. 6, bibl. 10 (in English, summaries in English, Russian and Lithuanian).